Evaluation of sperm quality in young men in North Macedonia - Kostadinova Petrova, Irena; Kakasheva-Mazhenkovska, Lena; Mitevska, Elida; Tasheva, Ljubica; Stojkovska, Natasha (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2023)
Research data show that in the last 50 years (1938-1991) there has been a trend of decreasing sperm concentration in the male population in Europe by 2.3% and in the USA by 0.8%. The reasons for such negative trend are not known, but it is assumed that lifestyle and environmental factors have an influence on genetic factors. Aim of this study was to evaluate sperm quality in young, healthy men in our country, and to compare sperm quality in our population with others in the world. Material and methods: Ejaculates from 203 healthy male subjects, aged 18-32, were stored in a thermostat at 360 C and analyzed manually on a native slide and hematoxylin-eosin-stained slides, under a phase contrast microscope. Sperm motility was assessed at two-time intervals, group A, 60 minutes after ejaculation and group B, 120 minutes after ejaculation, while sperm concentration and sperm morphology were assessed at one time interval. Results:Semen analysis showed an average volume of ejaculate3.45 ± 1.5 ml, sperm concentration in 1 milliliter62.4 ± 39.2 x10(6) /ml, while total sperm concentration was 211.2 ± 173.2 x10(6). In group A, values for progressive spermatozoa were 48.6 ± 18.1 x10(6) /ml and in group B, values for progressive spermatozoa were 47.9 ± 17.3 x10(6) /ml. There was no statistically significant difference between the two time intervals (group A and group B) when interpreting sperm motility, p>0.005. Analysis of morphology of spermatozoa showed a mean value of 6.9% for morphologically normal spermatozoa. Conclusion: The quality of ejaculate in young men in North Macedonia is in the range of reference values according to WHO, and also our results are similar to those from Germany, Turkey, Bulgaria, Faroe Islands.
ЕВАЛУАЦИЈА НА ЕЈАКУЛАТОТ КАЈ МЛАДА, ЗДРАВА ПОПУЛАЦИЈА ВО РЕПУБЛИКА МАКЕДОНИЈА
Keywords: sperm motility; sperm concentration; sperm morphology